Analytical homogenization for stretch and bending of honeycomb sandwich plates with skin and height effects. (February 2015) - Li, Y.M.; Hoang, M.P.; Abbes, B.; Abbes, F.; Guo, Y.Q.
Abstract: The honeycomb sandwich plates are widely used in the automotive, aeronautic and aerospace industries. However, the numerical modeling of honeycomb structures is too tedious and time consuming. The homogenization of these structures enables to obtain an equivalent homogeneous solid and its elastic moduli thus to make very efficient simulations. In the present study, the skin effect is taken into consideration for the stretching and bending problems, in which the two skins are much more rigid than the honeycomb core. An analytic homogenization method, using trigonometric function series is proposed to study the influence of the honeycomb height on the elastic properties, and the upper and lower bounds of the equivalent elastic moduli of their curves are found compatible with those obtained by the membrane theory. The interfacial stresses are also studied in order to compare with the existing model for the stretching problem. Numerical H-models are established for the stretching, bending and the stretch–bending coupled problem respectively, and a very good agreement has been achieved between the results of the present H-models and 3D FE modeling.